2005
DOI: 10.1111/j.1462-5822.2005.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is an immediate macrophage response to Legionella pneumophila

Abstract: SummaryAfter ingestion by macrophages, Legionella pneumophila enter spacious vacuoles that are quickly enveloped by endoplasmic reticulum (ER), then slowly transferred to lysosomes. Here we demonstrate that the macrophage autophagy machinery recognizes the pathogen phagosome as cargo for lysosome delivery. The autophagy conjugation enzyme Atg7 immediately translocated to phagosomes harbouring virulent Legionella . Subsequently, Atg8, a second autophagy enzyme, and monodansyl-cadaverine (MDC), a dye that accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
270
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 267 publications
(273 citation statements)
references
References 83 publications
1
270
0
2
Order By: Relevance
“…CASP4 restricts the growth of L. pneumophila , an intracellular pathogen that resides in autophagosomes in WT macrophages [3,16,25]. Notably, B. cenocepacia is also cleared by autophagosomes in healthy macrophages [5], but the role of CASP4 in intracellular trafficking of this bacterium is not known.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CASP4 restricts the growth of L. pneumophila , an intracellular pathogen that resides in autophagosomes in WT macrophages [3,16,25]. Notably, B. cenocepacia is also cleared by autophagosomes in healthy macrophages [5], but the role of CASP4 in intracellular trafficking of this bacterium is not known.…”
Section: Resultsmentioning
confidence: 99%
“…The breakdown of damaged organelles and proteins via autophagy leads to the recycling of nutrients and sustains cellular energy levels. In addition, autophagy targets various intracellular pathogens such as Mycobacterium tuberculosis [1], Salmonella enterica serovar Typhimurium [2], Legionella pneumophila [3], Streptococcus pyogenes [4], and Burkholderia cenocepacia [5]. This bacteria-specific autophagic process, designated xenophagy, promotes bacterial clearance and prevents cellular escape.…”
Section: Introductionmentioning
confidence: 99%
“…19 Likewise, immediately after L. pneumophila internalization, the autophagic markers Atg7 and Atg8 are recruited to the Legionella phagosomal compartment. 17 These results clearly indicate that similarities exist between these two pathogenic bacteria.…”
mentioning
confidence: 72%
“…An interesting new finding is that autophagy is activated by molecules secreted via the Legionella Type IV system, as indicated by the processing of Atg8 and the formation of autophagic vacuoles. 17 Similarly, we have observed that numerous LC3/Atg8 decorated vesicles are formed in Coxiella-infected CHO cells 19 and we have proposed that Type IV secretion of bacterial molecules activates autophagy in the host cell. A protein secreted by the Type III system in Salmonella also induced autophagy in infected macrophages.…”
mentioning
confidence: 79%
See 1 more Smart Citation